Sanitation and Enviromental Health in Traditional Snack Food Trader of Elementary School, Buntusu Village, Makassar City - Serli, Serli; Werdyaningsih, Endang; Yulis, Dian Meiliani; Mustari, Sahdan; Atika, Zummatul; Kunaryanti, Kunaryanti; Yusrianto, Yusrianto (International Journal of Health Sciences, 2023)
Many snacks do not meet health requirements and therefore threaten children's health. Most school children's snacks are traditionally processed foods sold by street vendors. The aim of this research is to determine the implementation of hygiene and sanitation among traditional snack food traders in the Buntusu Village Elementary School environment, Makassar City. This research is a descriptive study designed based on a cross sectional approach. The population in this study were all traditional snack food traders in the Buntusu Village Elementary School area, Makassar City. So it can be concluded that the distribution of respondent characteristics includes 73.9% of respondents aged 24-54 years, 52.2% of respondents are male, 47.8% of respondents have worked as traditional snack food traders for 1-10 years, There were 4.3% of respondents with the highest level of education, namely graduating from college, and 8.7% of respondents with the lowest education, namely not attending school. And 52.2% of respondents had good personal hygiene, while the remaining 47.8% of respondents had poor personal hygiene.